How community ART delivery may improve HIV treatment outcomes: Qualitative inquiry into mechanisms of effect in a randomized trial of community‐based ART initiation, monitoring and re‐supply (DO ART) in South Africa and Uganda. Issue 10 (8th October 2021) - Gilbert, Hannah N.; Wyatt, Monique A.; Pisarski, Emily E.; Asiimwe, Stephen; van Rooyen, Heidi; Seeley, Janet; Shahmanesh, Maryam; Turyamureeba, Bosco; van Heerden, Alastair; Adeagbo, Oluwafemi; Celum, Connie L.; Barnabas, Ruanne V.; et al.
Abstract: Introduction: UNAIDS fast track targets for ending the AIDS epidemic by 2030 call for viral suppression in 95% of people using antiretroviral therapy (ART) to treat HIV infection. Difficulties in linking to care following a positive HIV test have impeded progress towards meeting treatment targets. Community‐based HIV services may reduce linkage barriers and have been associated with high retention and favourable clinical outcomes. We use qualitative data from The Delivery Optimization of Antiretroviral Therapy (DO ART) Study, a three‐arm randomized trial of community ART initiation, monitoring and re‐supply conducted in western Uganda and KwaZulu‐Natal South Africa, to identify mechanisms through which community ART delivery may improve treatment outcomes, defined as viral suppression in people living with HIV (PLHIV). Methods: We conducted open‐ended interviews with a purposeful sample of 150 DO ART participants across study arms and study sites, from October 2016 to November 2019. Interviews covered experiences of: (1) HIV testing; (2) initiating and refilling ART; and (3) participating in the DO ART Study. A combined inductive content analytic and thematic approach was used to characterize mechanisms through which community delivery of ART may have contributed to viral suppression in the DO ART trial. Results: The analysis yielded four potential mechanisms drawn from qualitative data representing the perspectives and priorities of DO ART participants. Empowering participants to schedule, re‐schedule and select the locations of community‐based visits via easy phone contact with clinical staff is characterized as flexibility . Integration refers to combining the components of clinic‐based visits into single interaction with a healthcare provider. Providers" willingness to talk at length with participants during visits, addressing non‐HIV as well as HIV‐related concerns, is termed " a slower pace ". Finally, increased efficiency denotes the time savings and increased income‐generating opportunities for participants brought about by delivering services in the community. Conclusions: Understanding the mechanisms through which HIV service delivery innovations produce an effect is key to transferability and potential scale‐up. The perspectives and priorities of PLHIV can indicate actionable changes for HIV care programs that may increase engagement in care and improve treatment outcomes.